Concepts and Provisions For Recovery Of A Case Through A Justice-Based Restorative Approach By The Prosecutor's Regulation No. 15 In The Year 2020 - Daffa Elvaretta; Achmad Ghozali Nasid; Anisa Aulia Fitri; Yunisha Dena Putri (Green Publisher Indonesia, 2023)
Background: The Restorative Justice Approach is one of the solutions for settling criminal cases, namely by prioritizing the subject matter of criminal acts and carrying out settlements outside the court, as well as restoring the situation. The Attorney General's Office of the Republic of Indonesia issued a regulation in the form of Attorney General's Regulation Number 15 of 2020 concerning the Termination of Prosecution Based on Restorative Justice. Purpose: To find out and analyze the implementation of Restorative Justice by the Public Prosecutor regarding the Prosecutor's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice by looking at several requirements that must be met. Method: The research method used is normative juridical, the type of data used in this research is qualitative data, which is categorized into two types, namely primary data and secondary data. Results: Restorative Justice as an approach to peace between victims and perpetrators have occurred in many prosecution cases at the Prosecutor's Office. In this case, the prosecutor's office hears the community's voice and wants justice for people with weak economic conditions before the law. However, in this case, the Prosecutor's Regulation Number 15 of 2020 still has requirements for cases or perpetrators who can or cannot stop use based on restorative justice. Conclusion: Based on the results of the study it was concluded that the prosecutor's office listens to the voice of the community and wants justice for people whose economic conditions are weak before the law. However, the Prosecutor's Regulation Number 15 of 2020 still requires cases or actors who can or cannot stop use based on restorative justice.